Screening tests for hepatitis B virus, hepatitis C virus, and human immunodeficiency virus in blood donors: Evaluation of two chemiluminescent immunoassay systems. (September 2014) - Sommese, Linda; Sabia, Chiara; Paolillo, Rossella; Parente, Delia; Capuano, Maria; Iannone, Carmela; Cavalca, Francesco; Schiano, Concetta; Vasco, Maria; De Pascale, Maria Rosaria; Casamassimi, Amelia; Napoli, Claudio
Abstract Automated chemiluminescent immunoassays (CLIAs) are useful for the detection of hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus 1/2 antigen/antibodies (HIV 1/2 Ag/Ab) in blood donor screening. Eight hundred and forty serum samples were tested for hepatitis B surface antigen (HBsAg), HCV antibodies (anti-HCV), and HIV1/2 Ag/Ab in parallel using 2 different CLIAs (Abbott Architect i2000SR and Roche Cobas e411). The concordance between the 2 systems was high (Cohen's kappa 0.97 for HBsAg, 0.77 for anti-HCV, 0.92 for HIV1/2 Ag/Ab) and the specificity and the positive predictive value were comparable. Among the 12 discrepant results, 11 were false-positive and 1 (reactive by Architect) was true-positive for anti-HCV. Positivity for HBV DNA, HCV RNA, and HIV RNA was recorded in 90.9%, 38.9%, and 100% of true-positive samples, respectively. This study represents the first stringent comparison between Architect i2000SR and Cobas e411 in blood donors. We observed a good correlation and high agreement among HBV, HCV, and HIV with the 2 automated systems.